2014
DOI: 10.4236/ojts.2014.42011
|View full text |Cite
|
Sign up to set email alerts
|

A Pictorial Review on the Role of 64-Slice HD MDCT in Detecting Post CABG Cardiothoracic Complications

Abstract: Aims: The aim of this study is to have a pictorial review on the role of 64-slice multi-detector computerized tomography (MDCT) in detecting post coronary artery graft (GABG) cardiothoracic complications. Materials & Methods: During the period from November 2012 to December 2013, a prospective evaluation of 40 patients with suspected post-operative cardiothoracic complications underwent MDCT coronary angiography in our clinical radiology department. Informed consent was obtained from all patients and the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Hematoma, alone, is an important complication, as it can rarely compress the heart and arteries and may even cause superior vena cava syndrome ( 26 ) and tamponade, which lead to shock and death in the patients ( 27 ). Therefore, diagnosis is essential; previous studies have suggested CT scan as an accurate diagnostic tool for post-CABG epicardial and retrosternal hematoma formation ( 28 , 29 ). We could also detect the details of the developed hematoma by CT scan successfully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematoma, alone, is an important complication, as it can rarely compress the heart and arteries and may even cause superior vena cava syndrome ( 26 ) and tamponade, which lead to shock and death in the patients ( 27 ). Therefore, diagnosis is essential; previous studies have suggested CT scan as an accurate diagnostic tool for post-CABG epicardial and retrosternal hematoma formation ( 28 , 29 ). We could also detect the details of the developed hematoma by CT scan successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma, caused by the leaking of blood from an aneurysmectomy/aneurysmorrhaphy site, is listed among common postoperative complications of CABG; but not as a cause of post-CABG TdP. Hematoma, alone, is an important complication, as it can rarely compress the heart and arteries and may even cause superior vena cava syndrome (26) and tamponade, which lead to shock and death in the patients (27). Therefore, diagnosis is essential; previous studies have suggested CT scan as an accurate diagnostic tool for post-CABG epicardial and retrosternal hematoma formation (28, 29).…”
Section: Discussionmentioning
confidence: 99%